Digital glocalization: theorizing the twenty-first-century ICT revolution - Roudometof, Victor (Frontiers in Communication, 2023)
This paper offers an overview and theorization of digital glocalization that transcends past interpretations concerning the effects of ICT on techno-social relationships. It outlines a general theoretical framework that uses glocalization as a bridge between global and local. Digital glocalization might lead to the reconstruction of places through digital means or, alternatively, to newly found “third” spaces of glocal hybridity. This framework conforms to empirical evidence on how ICT reshapes the social world of the twenty-first century. Concrete manifestations of digital glocalization are reviewed in order to provide readers with suitable examples of its application in work and leisure environments. These range from internet governance to the entertainment industry. The growth and spread of ICT across the globe has the potential to lead to the construction or reconstruction of local places, whereby “placeness” can be created (or recreated); it can also create glocal hybrids that creatively combine online/offline experiences, such as diverse forms of geomedia and augmented reality technologies.